Interpreting measurements of physical function in clinical trials. (12th October 2007) - Ward, Michael M
Abstract : Improving physical functioning is one of the major goals of anti-rheumatic treatment. However, functional limitations can have several different causes, which may differ in their capacity to respond to a given treatment. Functional limitations due to pain or other acute symptoms or signs may be readily reversible with efficacious treatment, while those due to chronic structural changes may be relatively irreversible in the short term. Because measures of physical function characterise the degree of limitation without regard to cause, patients with the same apparent degree of functional limitation may differ greatly in their ability to demonstrate response to treatment. Structural damage accumulates over the course of disease, so measures of functional limitations tend to be less responsive among patients with more longstanding disease. This decreased responsiveness leads to a decreased ability to discriminate between treatments in patients with more longstanding arthritis. In addition, the criteria for minimal clinically important improvement may be underestimated when patients with irreversible functional limitations are included as test subjects, because judgments of improvement may be associated with smaller measured changes in physical functioning. The interpretation of measurements of physical function in clinical trials should consider the composition of the study sample, with attention to the stage of disease and the heterogeneity in disease duration or structural damage among subjects.